Ni-Catalyzed Addition of Arylborons to Alkenes for the Synthesis of Quaternary Carbon Centers - Wang, Zi-Chao; Wang, Peng; Shi, Shi-Liang (Synlett, 2025)
All-carbon quaternary centers are prevalent structural motifs, thus attracting increasing interest from the organic community. We present here a nickel-catalyzed, Markovnikov-selective addition of stable organoborons to simple alkenes, enabled by a diimine ligand. This robust method provides efficient access to quaternary carbon centers with high yields. Furthermore, with a bulky chiral diimine ligand, quaternary carbon stereocenters can be readily prepared. Mechanistic investigations indicate the involvement of an unusual nickel migration from an alkyl nickel to an aryl nickel species.
Keywords: Quaternary carbon centers; Nickel catalysis; Diimine ligand; Addition reaction; Organoborons